Association between functional status and self-care behavior among adults at high risk of stroke : A cross-sectional study - Anurak, Atid; Chaow, Chalermchai (Science Center Group, 2025)
Background: Stroke remains a major public health concern and a leading cause of mortality and long-term disability worldwide, particularly among individuals with chronic diseases living in rural areas. Self-care behavior plays an essential role in stroke prevention; however, limited evidence exists regarding how functional status influences the ability of high-risk individuals to engage in preventive health behaviors. Objective: This study aimed to examine the association between functional status and self-care behavior among adults at high risk of stroke in rural communities. Methods: A quantitative cross-sectional correlational study was conducted among 100 adults aged 30 years and older who were identified as having a high risk of stroke using the Thai Cardiovascular Risk Score (≥20%). Participants were recruited from ten health-promoting hospitals in rural Thailand using a multi-stage random sampling technique. Functional status and self-care behavior were assessed using validated self-report questionnaires. Data were analyzed using descriptive statistics and Pearson’s product–moment correlation to examine the relationship between the two variables. Results: Participants demonstrated moderate levels of functional status (M = 55.87, SD = 9.34) and self-care behavior (M = 65.42, SD = 6.78). Pearson’s correlation analysis revealed a statistically significant positive relationship between functional status and self-care behavior (r = 0.392, p < 0.001), indicating that individuals with higher functional capacity were more likely to engage in stroke-preventive behaviors such as medication adherence, healthy diet, physical activity, and stress management. Conclusion: Functional status is an important determinant of self-care behavior among adults at high risk of stroke. Interventions aimed at maintaining or improving functional capacity may enhance self-care practices and contribute to more effective stroke prevention strategies, particularly in rural communities with limited healthcare access.